PENGARUH PENGANGGURAN, JUMLAH PENDUDUK, DAN PENDIDIKAN TERHADAP KEMISKINAN DI PROVINSI SUMATERA BARAT - Lili Salfina; Fatria Destika (Universitas Sumatera Barat, 2021)
The research object that the writer chose was West Sumatra. This study aims to see how the effect of unemployment, population, and population education in West Sumatra Province partially and simultaneously. The data used are secondary data for 2009 – 2019 obtained from the West Sumatra Central Statistics Agency. The data analysis technique used is multiple regression analysis processed using the IBM SPSS 23 program. The formulation of the results of the analysis is Y = 56,569 + 0,603 X1 – 2,462 X2 – 0,505 X3. The results of this study indicate that unemployment partially has a positive and significant effect on poverty, population has a significant negative effect on society, education has a negative and insignificant effect on poverty. And simultaneously unemployment, population, and education have a significant effect on poverty in West Sumatra Province, with the independent variable contribution of 84.2%.